Developing Ireland: Committing to economic openness and building domestic institutional capabilities - Paul Teague (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2009)
This paper sets out to explain the factors behind Ireland's exceptional period of economic growth from the early 1990s to the mid 2000s. It suggests that an unbending commitment to economic openness and an on-going effort to establish quality domestic institutions were the main drivers of the so-called Celtic tiger phenomenon. The commitment to economic openness manifested itself in the relentless search for inward investment and a willingness to accept deep forms of European integration. Building domestic institutional capabilities involved adopting new-classical macroeconomic policies, creating a robust system of social partnership and reforming the educational system. The two factors positively interacted with each other to create dynamic effects.
Keywords: E02; F23; J58; O52; P16; 330; Ireland; economic growth; economic development; inward investment; economic systems; Wirtschaftswachstum; Wirtschaftliche Anpassung; Irland